Obesity and overweight and associated factors among women with infertility undergoing assisted reproductive technology treatment in a low income setting - Christian Amoah; Rudolph Kantum Adageba; Ernest K. Appiah; Promise E. Sefogah (Scientific Reports, 2025)
Abstract Elevated Body Mass Index in infertile women has important implications for medically assisted reproduction. The prevalence and impact of elevated BMI on assisted reproductive technology treatment outcomes in low-income settings remain under-studied and little known. This study investigated the prevalence of elevated BMI and associated socio-demographic characteristics among infertile women in Ghana. Retrospective analysis of five-years data of 3,660 infertile women attending clinic in Ghana for assisted conception treatment was carried out. The data was analysed using the SPSS-22; descriptive statistics performed and chi square used to assess associations between categorical variables, p-value below 0.05 was considered statistically significant. Overall, 76.83% of women with infertility had elevated BMI, of whom 39.56% were obese and 37.27% were overweight. Majority of participants with elevated BMI was aged between 30–49 years. (p < 0.001). Infertility prevalence and BMI increased with increasing level of education (p < 0.003). Secondary infertility was more common among overweight or obese women. Traders had the highest prevalence of overweight and obesity followed by civil servants and health workers. Elevated BMI was highly prevalent among women seeking infertility care in Ghana, particularly so among those with secondary infertility. Traders had the highest prevalence of elevated BMI, probably reflecting their predominantly sedentary lifestyles.